Disagreements in society over linear vs. over nonlinear labour-income tax schedules - Asen Ivanov (Queen Mary University of London, School of Economics and Finance, 2024)
I investigate numerically the following question: Given that individuals with different wages disagree over the optimal labour-income tax schedule, how would such disagreements be affected if society restricted itself to using linear tax schedules? I find that there would be (i) a decrease in disagreements within a large segment of the population at the top of the wage distribution, (ii) a sharp decrease in how much a very-high-wage individual disagrees with individuals whose wage is weakly above the median but sufficiently far below her wage, (iii) a sharp decrease in how much a zero-wage individual disagrees with a median-wage individual, and (iv) a decrease in how much a zero-wage individual disagrees with high-wage individuals.
Keywords: D70; D72; D74; H20; 330; labour-income tax; linear tax; redistribution; conflict